The relationship between share price of consumer products and industrial products with economic growth in Malaysia (1991- 2013) / Nor Juliana Saadin and Mohamad Hafiz Pheros - Saadin, Nor Juliana; Pheros, Mohamad Hafiz (Faculty of Business and Management, 2014)
This paper is a fresh attempt to investigate the relationship between stock market and economic growth in Malaysia. This study identifies whether Share Price of Consumer Products and Industrial Products have affected the economic growth or not. The previous study has shown that, there was homogenous result on the relationship of Share Price of Consumer Products and Industrial Products and economic growth. Share price (independent variable) data as the indicator of stock market performance was collected from Datastream database, and country’s gross domestic product (GDP) as the indicator of economic growth (dependent variable) from the website. In this study, we use Single Linear Regression Method from first quarter 1991 until fourth quarter 2013 of the share price.